Mandibular Canal Widening and Bell's Palsy: Sequelae of Perineural Invasion in Oral Cancer. (29th November 2016) - Sundar, Gopinath Thilak Parepady; Sherigar, Vishwanath; Shetty, Sameep S.; Satya, Shree; Gohil, Sourabh M.
Abstract : Perineural invasion is an underrecognized route of metastatic spread along the nerve bundles within the nerve sheath into the surrounding tissues. It hinders the ability to establish local control as tumour cells can traverse along nerve tracts well beyond the extent of any local invasion rendering them inoperable and unresectable. Perineural invasion is a marker of poor prognosis. Oral submucous fibrosis with oral cancer constitutes a clinicopathologically distinct disease. Our case highlights an enigmatic presentation of oral submucous fibrosis and its coexistence with oral cancer presenting with unusual neurological disturbance of the inferior alveolar nerve and facial nerve and diffuse widening of the mandibular canal. The objective of this case report is to enumerate the significance of perineural invasion in determining the course of the disease and necessitate the need for future studies that can shed light on molecular mediators and pathogenesis of perineural spread.